1986
DOI: 10.1093/infdis/154.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Hepatitis B Virus (HBV) DNA Positivity in Chronic HBV Infection: Results of a Long-Term Follow-Up Study of 138 Patients

Abstract: In an assessment of the clinical relevance of serum hepatitis B virus (HBV) DNA testing in chronic HBV infection, changes in the presence of this marker were investigated by spot hybridization in 138 hepatitis B surface antigen (HBsAg)-positive patients with chronic liver disease who were followed up for one to eight years. Forty-one patients were treated with steroids, often with evidence of potentiation of viral replication, whereas 92 patients remained untreated and had no evidence of sigma agent infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Four such occurrences were detected in this study, and none were associated with abnormal ALT values. These findings corroborate those from previous studies in Asian children with HBV (20) and differ from findings in adults in whom episodes of active virus replication after loss of HBeAg are frequently accompanied by severe abnormalities in liver function tests and liver histological findings (4,16,17,21,22).…”
Section: Discussionsupporting
confidence: 90%
“…Four such occurrences were detected in this study, and none were associated with abnormal ALT values. These findings corroborate those from previous studies in Asian children with HBV (20) and differ from findings in adults in whom episodes of active virus replication after loss of HBeAg are frequently accompanied by severe abnormalities in liver function tests and liver histological findings (4,16,17,21,22).…”
Section: Discussionsupporting
confidence: 90%
“…We have reported that replication of HCV occurs even in advanced or late stages of liver disease (11). In HBV infection, the replicative level of HBV usually declines with time (19). In contrast, quantitation of circulating HCV RNA revealed that the serum concentration of HCV was higher in patients with CAH, cirrhosis or HCC than in patients with CPH or asymptomatic blood donors.…”
Section: Discussionmentioning
confidence: 98%
“…[20][21][22][23][24][25][26][27][28][29] In addition, histological assessments of patients in other studies of lamivudine have shown that liver biopsy features improve significantly during lamivudine-induced suppression of HBV replication. 5,30,31 Further controlled trials of prolonged lamivudine treatment are in progress to define the efficacy and safety of lamivudine therapy and maintenance of virological responses after drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%